Carotid Artery Stenting in Patients With Acute Coronary Syndrome: A Possible Primary Therapy for Symptomatic Carotid Stenosis. (August 2013) - Casana, Renato; Halliday, Alison; Bianchi, Paolo; Fresa, Emanuele; Silani, Vincenzo; Parati, Gianfranco; Blengino, Simonetta; Cireni, Lea; Adobbati, Laura; Calvillo, Laura; Tolva, Valerio S.
Purpose: To report the results of carotid artery stenting (CAS) in symptomatic patients (stroke/transient ischemic attack) after recent percutaneous transluminal coronary angioplasty (PTCA) for acute coronary syndrome (ACS). Methods: Between January 2009 and July 2011, 28 consecutive patients (18 women; mean age 66 years, range 42–82) underwent protected CAS for symptomatic carotid stenosis following recent PTCA that included bare or drug-eluting stents requiring uninterrupted dual antiplatelet therapy. Primary technical success, neurological complications, major adverse cardiovascular events, and death were evaluated at 30 days and over midterm follow-up. Results: Technical success was 96%; 1 patient suffered a nonfatal major stroke (3.5% 30-day stroke rate) during the procedure. During a median 21.6-month follow-up, 4 (14%) patients died of myocardial infarction (all diabetic smokers with ejection fractions <40%), but there were no new neurological events. Estimated survival was 89.3% at 2 years. Further coronary interventions were performed in 2 diabetic patients with a body mass index >34 kg/m 2 . Conclusion: This preliminary experience demonstrated that CAS is a reasonable, safe, and effective treatment for patients with symptomatic carotid artery stenosis who were recently treated with coronary stents requiring uninterrupted dual antiplatelet therapy.